Effect of combined microwave heating and impinging hot-air on rubberwood drying - Thanate Ratanawilai (Advanced Materials Research, 2012)
Applying microwave heating and impinging hot-air is one of the most interesting methods to increase the higher drying rates of rubberwood drying based on acceptable quality. A maximum microwave power level of 200W at a frequency of 2.45GHz with maximum working temperature of 70°C, only hotair (70°C) and combined microwave (200W) - hotair (70°C) were choosed to evaluate the effect of rubberwood drying by different width sizes (1, 2, 3 and 4 in.) by 46 in. length by 1 in. thick. In all cases, the drying time is reduced significantly from 168 h to less than 8-15 h in various wood widths and resulted in saving to an extent of about 91% of drying time from initial moisture content ranges of 73%-49% to 15% percent of moisture level. Drying stresses from prong test no found during drying and total color of rubberwood changed after high temperature drying is a natural surface when compared to fresh wood. The values of six strength compared to the reference values are concentrated in the ranges of 16.9-23.9 (11.0)MPa for shearing strength parallel to grain, 4291.1-6701.6 (4350)N for hardness, 73.3-110.2 (66.0)MPa for MOR, 7059.5-12856.7 9240.0) MPa for MOE, 27.2-14.3 (5.0)MPa for compressive strength perpendicular to grain and 60.6-35.7 (32.0)MPa for compression strength parallel to grain. These results show that it is possible to develop a drying process for rubberwood using microwave-hot air in investigating further in this area.